IMPLEMENTATION OF THE CONTENT MARKETING STRATEGY BY SMJ BY MBOK JUDES BANYUWANGI TO INCREASE CUSTOMER ENGAGEMENT - Nurcahya Ningsih, Rosita; Wahyuni, Sri; Zulianto, Mukhamad; Prasetyo, Hery (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2023)
Technological advances are an opportunity for the regional culinary industry to develop along with the development of marketing 4.0 which makes this culinary subsector more competitive. Social media marketing is one type of digital marketing that is often used by culinary business actors in promoting. One of them is by implementing content marketing. Based on the results of the study stated that the main purpose of content marketing strategy is to increase customer engagement. This research is a qualitative descriptive study conducted at the SMJ by Mbok Judes restaurant, Banyuwangi District, Banyuwangi Regency. This study uses a snowball sampling technique in determining informants. SMJ by Mbok Judes Banyuwangi generates customer engagement through consumer responses to content marketing which is mapped into 3 dimensions including cognitive, affective, and behavioral engagement. Cognitive involvement in the form of the level of consumer interest in the content and information from the content. Affective engagement is formed based on consumer enthusiasm and satisfaction with the content. Behavioral engagement is based on sharing and supporting content behavior.